Assessment of Recovery of Milk Protein Allergens from Processed Food for Mass Spectrometry Quantification. (23rd November 2019) - Groves, Kate; Cryar, Adam; Walker, Michael; Quaglia, Milena
Abstract: Assessing the recovery of food allergens from solid processed matrixes is one of the most difficult steps that needs to be overcome to enable the accurate quantification of protein allergens by immunoassay and MS. A feasibility study is described herein applying International System of Units (SI)-traceably quantified milk protein solutions to assess recovery by an improved extraction method. Untargeted MS analysis suggests that this novel extraction method can be further developed to provide high recoveries for a broad range of food allergens. A solution of α-casein was traceably quantified to the SI for the content of α-S1 casein. Cookie dough was prepared by spiking a known amount of the SI-traceable quantified solution into a mixture of flour, sugar, and soya spread, followed by baking. A novel method for the extraction of protein food allergens from solid matrixes based on proteolytic digestion was developed, and its performance was compared with the performance of methods reported in the literature.